Réponses

  • Omnes
  • Modérateur confirmé
2014-05-13T23:20:17+02:00
Salut,

(4x-3)² - 9 = 0

Pour x = 3/4 :

(4*3/4 - 3)² - 9 = (3-3)² - 9 = 0² - 9 = -9
-9 ≠0, 34 n'est pas solution de l'équation.

Pour x = 0;

(4*0 - 3)² - 9 = (0-3)² - 9 = (-3)² - 9 = 9-9 = 0
0 est solution de l'équation.

2.

(4x-3)² - 9 = 16x² - 24x + 9 - 9 = 16x² - 24x
4x(4x-6) = 16x² - 24x

On a donc : (4x-3)² - 9 = 4x(4x-6)

3.

On sait que (4x-3)² - 9 = 4x(4x-6)
On veut que 4x(4x-6) = 0
4x = 0
x = 0

4x - 6 = 0
4x = 6
x = 6/4 = 3/2.

Bonne soirée!